Invasive species of Amphipoda (Crustacea, Malacostraca) in Ohrid Lake Basin (Contribution to the Knowledge of the Amphipoda 265) - Karaman, Gordan (Macedonian Journal of Ecology and Environment, 2013)
Fauna of Amphipoda in ancient Ohrid Lake in Macedonia is highly endemic, with nearly 12 endemic species of various origin. Among non endemic species in Ohrid Lake two species are invasive species: Orchestia cavimana Heller, 1865 (sensu auct.), originated from the sea and Gammarus roeselii Gervais, 1835 originated from SE Europe and Asia Minor. Orchestia cavimana is recent invader, observed in Ohrid Lake at the first time in 1998 and now this species settles numerous shores of the Lake, covered by gravel and sand. Gammarus roeselii invaded Ohrid Lake probably after the last Glacial period, and it was observed in Ohrid already in 1924. This species settled numerous small torrents and springs along the entire Lake Ohrid, often in mixed populations with native species. It penetrated also into the Lake itself on some shores (Struga) till 20 m depth. The present molecular and genetic investigations of both species suggest that probably several taxa exist under the names Orchestia cavimana (sensu auct.) and Gammarus roeselii (sensu auct.). The influence of both taxa on the native Amphipoda species in Ohrid Lake is still unknown.